UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL LIMBAH KULIT BUAH APEL (Malus domestica Borkh.) TERHADAP RADIKAL BEBAS DPPH (2,2-Diphenyl-1-Picrylhydrazil) - Ratih Dyah Pertiwi; Cut Ervinar Yari; Nanda Franata Putra (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Recently, many plants have not been utilized properly, one of those is apple plant. There are several types of apples which are widely consumed and used as processed products, among others, as candied apples, syrup and fruit juice. The effluent from the process in the form of processed peel and pulp is not only used as a substitute for animal feed and fertilizer plants, but also used as a natural antioxidant that is needed by the human body against various free radical. Most of the people who like to consume apples prefer to discard the apple peel without using it. Apple peel contains quercetin substances, which needed to increase the levels of antioxidants. The preparation of ethanol extract from apple peels waste is used by maceration method using solvent 70% ethanol. To test the antioxidant activity towards free radical DPPH the extract was made into several concentrations, namely 10 ppm, 20 ppm, 30 ppm, 40 ppm and 60 ppm, and than mixed with a solution of DPPH with concentration of 100 ppm. The absorbance was measured using a spectrophotometer UV-Visible. Based on the result of the research, the percentage of reduction obtain from those of extract concentrations were 8.580%, 14.510%, 21.653%, 26.685% and 34,232%. From percentage reduction result, it was obtain IC50 in the amount of 87.795 ppm. Based on the IC50 values can be conclud that the ethanol extract of apple peel waste has strong antioxidant activity classification